The Playing Of Vasilli Svietlovidoff's Character In Anton P. Chekhov's Swan Song Translation Of Djohan A Nasution With Method Of Acting The Stanislavski System - Lubis, Abdul Haris; Susanti, Desi; Alamo, Enrico (Institut Seni Indonesia Padangpanjang, 2023)
Playing the character Vasilli Svietlovidoff in the script